Recenzja książki Ryszarda A. Stefańskiego pt: „Obrona obligatoryjna w polskim procesie karnym”, Oficyna a Wolters Kluwer business, Warszawa 2012: Book Review of Richard A. Stefański entitled „Defense obligatory in Polish criminal process”, Publishing a Wolters Kluwer business, Warsaw 2012 - Pawelec, Kazimierz J. (Management and Administration Journal, 2021)
x